Cover Image, Volume 59, Issue 2. Issue 2 (7th January 2020) - Li, Jun; Dubois, Wendy; Thovarai, Vishal; Wu, Zhijie; Feng, Xingmin; Peat, Tyler; Zhang, Shuling; Sen, Shurjo K.; Trinchieri, Giorgio; Chen, Jichun; Mock, Beverly A.; Young, Neal S.
Abstract : The cover image is based on the Original Article Attenuation of immune‐mediated bone marrow damage in conventionally‐housed mice by Beverly Mock, Tyler Peat, Wendy DuBois et al., https://doi.org/10.1002/mc.23151 .